A Randomized Controlled Open Trial of Population-based Disease and Case Management in a Medicare Plus Choice Health Maintenance Organization - David C. Martin; Marc L. Berger; David T. Anstatt; Jonathan Wofford; DeAnn Warfel; Robin S. Turpin; Carolyn C. Cannuscio; Steven M. Teutsch; Bernard J. Mansheim (Centers for Disease Control and Prevention, 2004)
Introduction The object of this study was to examine the effect of population-based disease management and case management on resource use, self-reported health status, and member satisfaction with and retention in a Medicare Plus Choice health maintenance organization (HMO). Methods Study design consisted of a prospective, randomized controlled open trial of 18 months duration. Participants were 8504 Medicare beneficiaries aged 65 and older who had been continuously enrolled for at least 12 months in a network model Medicare Plus Choice HMO serving a contiguous nine-county metropolitan area. Members were care managed with an expert clinical information system and frequent telephone contact. Main outcomes included self-reported health status measured by the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), resource use measured by admission rates and bed-days per thousand per year, member satisfaction, and costs measured by paid claims. Results More favorable outcomes occurred in the intervention group for satisfaction with the health plan (P < .01) and the social function domain as measured by SF-36 (P = .04). There was no difference in member retention or mortality between groups. Use of skilled nursing home services was significantly lower in the intervention group than in the control (616 vs 747 days per thousand members per year, P = .02). This reduction, however, did not lead to lower mean total expenditures in the intervention group compared with the control ($6828 per member for 18 months vs $7001, P = .61). Conclusion Population-based disease management and case management led to improved self-reported satisfaction and social function but not to a global net decrease in resource use or improved member retention.